2020
DOI: 10.1002/cjoc.202000385
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Prospects of Surface Modification on Nickel‐Rich Materials for Lithium‐Ion Batteries

Abstract: Although layered Ni-rich cathode materials have attracted lots of attention for their high capacity and power density, several significant issues, such as poor thermal stability and moderate cyclability, limit their practical applications. Most of these undesired problems of Ni-rich materials are caused by the unstable surface or the parasitic reactions at cathode-electrolyte interface. Surface coating is the most common method to suppress such interfacial problems for Ni-rich materials. This review focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 168 publications
0
5
0
Order By: Relevance
“…The positive impacts originate from the synergistic effects of suitable LiTaO 3 coating and Ta 5+ doping as long as the fast ion‐conductor coating layer and the enlarged inter‐planar spacings could not only modify the interfaces and accelerate the transfer of Li‐ions, but also prevent the direct contact between electrolyte and electrode, decreasing the parasitic reactions and thus improving the cycling stabilities and rate performances of Ni‐rich materials [18] . However, the electrochemical performances of LTO‐3 and LTO‐4 at 10 C rate are abnormal and unexpected because the coating of fast ion‐conductor layer is always beneficial to the electrochemical performances of Ni‐rich materials [5d,19] . Herein, combined with the scanning electron microscopy (SEM) and TEM results, we can conclude that even though the LiTaO 3 is one kind of faster lithium‐ion conductor, and the self‐agglomeration and scattering of over‐added of LiTaO 3 will prolong the transfer length of Li ions, worsening the electrochemical kinetics and deteriorating the electrochemical performances of Ni‐rich materials.…”
Section: Resultsmentioning
confidence: 99%
“…The positive impacts originate from the synergistic effects of suitable LiTaO 3 coating and Ta 5+ doping as long as the fast ion‐conductor coating layer and the enlarged inter‐planar spacings could not only modify the interfaces and accelerate the transfer of Li‐ions, but also prevent the direct contact between electrolyte and electrode, decreasing the parasitic reactions and thus improving the cycling stabilities and rate performances of Ni‐rich materials [18] . However, the electrochemical performances of LTO‐3 and LTO‐4 at 10 C rate are abnormal and unexpected because the coating of fast ion‐conductor layer is always beneficial to the electrochemical performances of Ni‐rich materials [5d,19] . Herein, combined with the scanning electron microscopy (SEM) and TEM results, we can conclude that even though the LiTaO 3 is one kind of faster lithium‐ion conductor, and the self‐agglomeration and scattering of over‐added of LiTaO 3 will prolong the transfer length of Li ions, worsening the electrochemical kinetics and deteriorating the electrochemical performances of Ni‐rich materials.…”
Section: Resultsmentioning
confidence: 99%
“…The selected area electron diffraction (SAED) image (Figure b) indicates the characteristic layered structure mixed with a secondary phase detected in the as-prepared 622@LZPO particle. According to fast Fourier transform combined with the inverse fast Fourier transform analysis (Figure S3a,b), the interior region I (red rectangular) exhibits the layered phase ( R -3 m space group) of LiTMO 2 (lithium transition metal oxides); meanwhile, the near surface region II (yellow rectangular) presents the Fm -3 m space group which often appeared in various surface doping cases. , Element mapping images (Figure S3c) and line-scan profile (Figure c) based on EDS demonstrate that the signal of the Zr element can be distinctly detected, and its intensity is decreased from the surface to the interior of one 622@LZPO particle. Herein, it is suggested that the Zr doping might have occurred during LZPO modification, which usually facilitates the formation of Fm -3 m phases in the near surface region II.…”
Section: Resultsmentioning
confidence: 99%
“…The scavenger of acidic HF leads to the dissolution of transition metal ions out of the surface of the active material, causing lattice damage and continuous loss of active material. [ 55c,e,80 ] During (de)lithiation, the coating layer could help to suppress the phase transition of cathodes from a layered structure to a rock‐salt phase because the presence of the physical layer can prevent the loss of oxygen from the lattice by preventing the reaction between reactive Ni 4+ and electrolyte. [ 81 ] Although core–shell materials cannot directly suppress the intergranular and intragranular cracking, it reduces effects of lattice expansion along the c ‐axis and shrinkage along the a‐axis and b‐axis.…”
Section: Solving Cathode Challenges By Core–shell Strategiesmentioning
confidence: 99%